2016
DOI: 10.1007/s11701-016-0621-9
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted hysterectomy for endometrial and cervical cancers: a systematic review

Abstract: Total and radical hysterectomies are the most common treatment strategies for early-stage endometrial and cervical cancers, respectively. Surgical modalities include open surgery, laparoscopy, and more recently, minimally invasive robot-assisted surgery. We searched several electronic databases for randomized controlled trials and observational studies with a comparison group, published between 2009 and 2014. Our outcomes of interest included both perioperative and morbidity outcomes. We included 35 observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 69 publications
1
15
0
Order By: Relevance
“…Some of these meta‐analyses include registry studies even though some analyse the same databases and include patients reported in the institutional cohorts. However, the findings of less operative conversions, lower blood loss, and a shorter hospital stay are consistent findings within meta‐analyses but this study also demonstrates less overall complications in the robotic arm as well as higher costs …”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Some of these meta‐analyses include registry studies even though some analyse the same databases and include patients reported in the institutional cohorts. However, the findings of less operative conversions, lower blood loss, and a shorter hospital stay are consistent findings within meta‐analyses but this study also demonstrates less overall complications in the robotic arm as well as higher costs …”
Section: Discussionsupporting
confidence: 84%
“…Other recent reviews and meta‐analyses of the subject exist . They do not include all the citations that are in this study nor the randomized controlled study.…”
Section: Discussionmentioning
confidence: 99%
“…108 These most recent findings stand in contradiction to the earlier referenced series that had suggested therapeutic equivalency of MIS compared with open approaches along with the MIS-associated potential advan-tages of decreased hospital stay and more rapid patient recovery. 101,102,104,105,[109][110][111][112] Given the recently presented findings of poorer oncologic outcomes and survival with the MIS techniques compared with open laparotomy, women should be carefully counseled about the oncologic risks and potential short-term benefits of the different surgical approaches.…”
Section: Minimally Invasive Surgical Approachesmentioning
confidence: 99%
“…6,7 On the other hand, minimally invasive surgery is the treatment of choice for the majority of patients with endometrial cancer, either using traditional or robotic-assisted technique. Although in general no significant differences in the number of pelvic and para-aortic nodes harvested using either technique have been found, 8 especially in obese women PALND is challenging to perform using the traditional approach, and the number of conversions has been lower in robotic-assisted surgery than in traditional laparoscopic surgery. 9,10 This study was undertaken as a quality-control measure to evaluate the technical and surgical outcomes of PALNDs performed at our hospital.…”
mentioning
confidence: 90%